Performance Evaluation of Heterojunction SOI-Tunnel FET with Temperature - Chander S.; Sinha S.K.; Kumar S.; Singh P.K.; Baral K.; Singh K.; Jit S. (My University, 2025)
This paper investigates the impact of the temperature variation on Ge/Si heterojunction Silicon-on-Insulator (SOI) Tunnel Field Effect Transistor (TFET). The proposed device exhibits better performance in comparison with homojunction of the same device for different temperature. The effect of temperature is studied in terms of DC analysis as well as on AC analysis such as input characteristics, output characteristics, drain current, subthreshold swing (SS), threshold voltage, ION/IOFF ratio, transconductance, transconductance-to-drain-current-ratio, gate capacitance. This study reveals that OFF current of the device is independent of drain voltage variation irrespective of temperature variation. A small change in SS with temperature variation shows the weaker dependence of SS on temperature. A small variation in analog parameters with temperature variation shows that the device could be used for the high-temperature applications. A broad range of temperature from 200 K to 400 K has been used to analyze the performance of the device using Synopsys Technology Computer Aided Design (TCAD) simulation tool. © 2017 IEEE.